A Quest for True Islam A Study of the Islamic Resurgence Movement among the Youth in Bandung, Indonesia - Rosyad, Rifki (ANU Press, 2006)
This study presents the contemporary Islamic resurgence movement among young people in Bandung Indonesia, focusing on its emergence, development and routinisation. It traces various factors and conditions that contributed to the emergence of the movement. It also tries to explain how and why young people (students in particular) turn to Islam, and how the movement is organised and developed among students. Finally, it examines internal changes among various Islamic groups as responses to social, political and cultural changes.